DETERMINATION OF FIRM VALUE USING ECONOMIC VALUE-ADDED METHOD - Esin YELGEN (Fırat University, 2019)
With the latest developments in capital markets, the gradual rise in the tendencies of enterprises to public offering and reasons like business combinations and purchasing besides growth in franchising operations canalized stake holders to seeking correct calculation of firm value. Today determination of how much the actual value of the enterprise is has become one of the most important problems of the accounting-finance field from the perspectives of the buyer and the seller person or institution. On one hand while the person or the institution to do the purchasing transaction wishes to buy the enterprise at the potential lowest price, on the other hand the person or institution to close the sale wants this price to be the potential highest one. Accordingly, finding out the allowable optimal purchase/sale price becomes more of an issue for both parties. Due to such reasons, in recent years, many methods have been developed under the adopted approaches towards appraisal of business and value increase - accounting-based, market-based and income-based -. With an increase in the number of operand enterprises in capital market, income-based approach giving healthier results is preferred rather than classical approach in valuation. One of the most significant of the methods developed under income-based approaches is Economic Value Added – EVA method based on economic profitability of the enterprises in appraisal of business. However, when the literature is reviewed, public held enterprises are seen to be generally preferred for practices. On the other hand, no sufficient study has been found on how the value is calculated in non-public enterprises. Therefore, in the current study, it is aimed to determine the value of a non-public accommodation establishment. Within this scope, in the study an accommodation establishment operating in Alanya is taken as a sample and the disposal value of the enterprise is determined using economic value-added method.